Victorine restoration essays on Hugh of St Victor, Richard of St Victor, and Thomas Gallus - Orsbon, David Allison; Porwoll, Robert J. (Cursor mundi, 2021)
The Victorines were scholars and teachers of philosophy, liberal arts, sacred scripture, music, and contemplation at the Abbey of Saint-Victor in Paris. This collection focuses on the three greatest Victorines: Hugh (d. 1141), who established the direction of the school; Richard (d. 1173), who developed Victorine contemplation; and Thomas Gallus (d. 1246), who culminated Victorine contemplative thought and transmitted it to other schools, especially the Franciscans. They offer an innovative revival of the Christian spiritual and intellectual tradition for their reforming pastoral mission in their urban setting and for the Church.00Their contemporaries saw the Victorines as beacons of spiritual love and intellectual richness. Later reformers and thinkers held their writings as touchstones of contemplative love, including, for example, Bonaventure, Thomas Aquinas, Jean Gerson, Thomas à Kempis, the 'Devotio Moderna', and many others. The writings of the Victorines found broad appeal among later medieval readers, as well as praise among early modern reformers, Protestant and Catholic alike. In recent decades, the Victorines have returned to scholarly attention and renewed appreciation. Scholarly studies, critical editions, and translation projects reveal the treasures of Victorine thought and spirituality.00This volume showcases the findings of recent research and scholarly advances in Victorine studies, offering new readers a 'status quaestionis' of the field. It also features new research by eminent experts in Victorine thought that points out promising directions for future research, thus offering important new findings for established specialists